Effect of the Combination of Whole-Body Neuromuscular Electrical Stimulation and Voluntary Exercise on Metabolic Responses in Human - Watanabe, Kohei; Yoshida, Takahiro; Ishikawa, Tomoki; Kawade, Shuhei; Moritani, Toshio (Frontiers in Physiology, 2019)
Purpose Since neuromuscular electrical stimulation (NMES) can recruit high-threshold motor units and enhance glucose metabolism, the combination of NMES and voluntary low-intensity exercise would induce both anerobic and aerobic energy consumptions and this type of exercise could be more efficient and effective than conventional exercise regimens. We aimed to investigate metabolic responses and muscle fatigue during whole body NMES (WB-NMES), voluntary exercise, and their combination. Methods The blood lactate concentration and maximal voluntary contraction were measured before and after specified exercises: WB-NMES (E), voluntary exercise (V), and their combination (VE), and expired gas was sampled during the exercises in thirteen healthy young men. Each exercise was conducted for 15 min and interval between exercise was >48h. Results Energy expenditure and VO2 relative to the body mass during VE were significantly higher than during V and E (p < 0.05). The Respiratory gas exchange ratio (RER) during both E and VE was higher than during V (p < 0.05), and the blood lactate concentration after VE was significantly higher than after V and E (p < 0.05). Although VO2 relative to the body mass was 18.6 ± 3.1 ml/min/kg and the metabolic equivalent was 5.31 ± 0.89 Mets, the blood lactate concentration reached 7.5 ± 2.7 mmol/L after VE. Conclusion These results suggest that the combination of WB-NMES and voluntary exercise can enhance the metabolic response to a level equivalent to high intensity exercise under the net physiological burden of low-middle intensity exercises.